Hepatic Sarcoidosis Complicated with Pancreatic Adenocarcinoma. (19th November 2019) - Gupta, Kamesh; Hassan, Tuyyab; Rizwan, Shahid; Hans, Bandhul; Jawale, Rahul; Desilets, David
Abstract : Sarcoidosis is a systemic noncaseous granulomatous disease. The liver is a common location but usually asymptomatic. Current literature suggests an association between sarcoidosis and cancers. However, there is a lack of definite evidence. We present a case of a 59-year-old man with jaundice and acutely elevated alkaline phosphatase. The diagnosis was confirmed by obtaining a liver biopsy and was treated with 6 months of steroids. A year later, he had a recurrence of jaundice. MRCP showed biliary dilatation and a mass in the pancreatic head, confirmed by biopsy to be adenocarcinoma. This is the first case to be reported of hepatic sarcoidosis associated with pancreatic cancer.